Perancangan model Holistic Mathematics Education (HME) berbasis pendekatan Realistic Mathematics Education (RME) pada siswa sekolah dasar (SD) kelas tinggi - Hayati, Rahmatul; Marfilinda, Riri; Prima, Wahyu; Wulandari, Suci; Oktama, Zora (Borobudur Educational Review, 2025)
This study aims to develop a Holistic Mathematics Education (HME) model based on the Realistic Mathematics Education (RME) approach, specifically designed for upper-grade elementary school students. The study adopts the Plomp development design, which consists of three main phases: (1) the Preliminary Phase, aimed at collecting empirical data to determine the characteristics of the model to be developed; (2) the Development Phase, aimed at designing and developing a valid and practical HME model based on the RME approach through a series of formative evaluations; and (3) the Assessment Phase, aimed at measuring the model's effectiveness in improving conceptual understanding, learning motivation, and students' character values. However, this research focuses solely on the design phase, producing outputs such as a model book, a teacher's guidebook, and a student's guidebook. The research instruments include validation sheets for both the instruments and the products, which were reviewed by experts to ensure their validity and reliability. This validation process ensures that the developed products have a strong theoretical foundation and are practically applicable in teaching mathematics at the upper elementary school level. The findings indicate that the developed products meet the criteria for validity and can thus be used for upper-grade elementary students. In subsequent stages, this model will be implemented with upper-grade students to assess its practicality and effectiveness.